2012
DOI: 10.4067/s0034-98872012001100001
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de metformina sobre la expresión del factor de necrosis tumoral-α, los receptores Toll-like 2/4 y la PCR ultra sensible en sujetos obesos con diabetes tipo 2

Abstract: Efecto de metformina sobre la expresión del factor de necrosis tumoral-a, los receptores Toll-like 2/4 y la PCR ultra sensible en sujetos obesos con diabetes tipo 2 RNA was isolated from these cells to measure expression of tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), Toll-Like Receptor 2/4 (TLR 2/4) and beta-2-microglobulin (B2M).Results: Thirty participants were studied. Of these, 16 subjects aged 54.4 ± 5.5 years were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Intriguingly, our study failed to show elevated serum TNFα, IL-6, IFNβ, IL-8, IL-10, IL-12 and IFNγ levels in T2DM subjects despite perturbations in cytokine/TLR mRNAs levels being evident in the monocytes and neutrophils taken from T2DM patients. In terms of TLR expression, studies have shown that metformin 33 , statins, PPAR-γ agonists 34 and angiotensin receptor blockers 35 lower the expression of TLR2 and TLR4 in T2DM patients. Further, previous studies have shown that insulin infusion significantly suppressed TLRs 1, 2, 4, 7, and 9 mRNA expressions in mononuclear cells obtained from T2DM individuals 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, our study failed to show elevated serum TNFα, IL-6, IFNβ, IL-8, IL-10, IL-12 and IFNγ levels in T2DM subjects despite perturbations in cytokine/TLR mRNAs levels being evident in the monocytes and neutrophils taken from T2DM patients. In terms of TLR expression, studies have shown that metformin 33 , statins, PPAR-γ agonists 34 and angiotensin receptor blockers 35 lower the expression of TLR2 and TLR4 in T2DM patients. Further, previous studies have shown that insulin infusion significantly suppressed TLRs 1, 2, 4, 7, and 9 mRNA expressions in mononuclear cells obtained from T2DM individuals 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Another secondary finding is that metformin is associated with an increased RA risk. This finding was unexpected because previous studies have found metformin to be associated with decreased levels of inflammatory markers 47 48 . However, hyperhomocysteinemia, which is a potential side effect of metformin 49 , has been found to be associated with elevated levels of immune activation markers in RA patients 50 .…”
Section: Discussionmentioning
confidence: 71%
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) will be the house-keeping gene. The primers to be used in the study are listed in Table 1, based on literature research [18–20]. …”
Section: Methodsmentioning
confidence: 99%